Analisis Kemampuan Pemecahan Masalah Siswa SMA Melalui Pemodelan Matematika pada Permasalahan Geometri - Erik Setiawan; Iqbal Kharisudin (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze high school students’ problem-solving abilities through mathematical modeling strategies in geometry problems. This research employed a descriptive qualitative approach involving 33 eleventh-grade students of SMA Negeri 12 Semarang, who were selected purposively based on variations in academic ability. Data were collected through written tests, observation, and in-depth interviews with nine selected students. The data were analyzed inductively by referring to the stages of mathematical modeling, namely understanding the problem context, mathematization, solving the mathematical model, interpreting the results, and validating the solution. The findings show that students’ ability to solve geometry problems through mathematical modeling varied according to the complexity of the problems. Students who answered correctly were able to identify relevant information, construct appropriate mathematical models, perform calculations, and interpret the results in accordance with the problem context. In contrast, students who answered incorrectly generally experienced difficulties in mathematization, applying geometry concepts, manipulating algebraic expressions, and validating final answers. The students’ success rate tended to decrease as the complexity of the problems increased. These findings indicate that transforming contextual problems into mathematical models and validating solutions are critical stages that require greater attention in mathematics learning based on mathematical modeling